Profile of female, household helpers their level of self-esteem, work values, life aspirations, and working conditions - Daplin, Rizalin T.
The study sought to examine the profile, levels of self-esteem, work values, life aspirations, and working conditions of selected female household helpers in Phase III, Alta Tierra Village, Jaro City. Thirty-eight (38) female household helpers served as respondents of the study., Five instrument were utilized for this study. An interview guide was used for profile, life aspirations and working conditions of female household helpers. Rosenberg Self-esteem Scale and Work Values Assessment Scale were also utilized for data gathering. The responses were analyzed through the frequency and mean to know life aspirations and work activities of the respondents. Results showed that majority of the respondents were single at their prime age of 15-20 years and their monthly salary ranged from Php 1,000-Php 2,000. They usually work for 12-13 hours a day and were given day-off anytime of the week. The respondents slept at around 9-10 p.m. and are together with their employers family. The reasons for employment were to support their families and the lack of other job opportunities. They evaluated themselves as having a high level of self-esteem. Intrinsically, they put high value on knowledge, expertise and precision work. In terms of extrinsic dimension, they aimed for financial gain and security in their job. Most of the respondents aspired to finish schooling and acquire high paying jobs to support their families. With regards to relationship with their employees, majority of them have no problem at all with the latter and almost all of them have access to household appliances.